Timing of active phase labor arrest diagnosis in nulliparous women: a cost-effectiveness analysis. (12th December 2022) - Schmidt, Eleanor M.; Hersh, Alyssa R.; Tuuli, Methodius; Cahill, Alison G.; Caughey, Aaron B.
Abstract: Background: Recommendations from the American College of Obstetricians and Gynecologists for the safe prevention of primary cesarean deliveries propose that cesarean delivery for active phase arrest in the first stage of labor should be performed only if women fail to progress despite four hours of adequate uterine activity and no cervical change. This is a change in recommendation from a two-hour threshold. Objective: To determine the economic and clinical implications of waiting four hours compared to two hours for cervical progression before diagnosing active phase labor arrest. Study Design: We designed a cost-effectiveness analysis using TreeAge Pro 2020 software with model inputs derived from the literature. We used a theoretical cohort of 1.4 million women, the approximate number of nulliparous U.S. women reaching four centimeters in spontaneous labor. We compared maternal and neonatal outcomes and costs associated with defining active phase arrest after four hours of no cervical progression versus two hours. As a baseline assumption, active labor was defined at four centimeters. It was assumed that women with active phase arrest were delivered via cesarean delivery. In addition to cost and maternal quality-adjusted life years (QALY), outcomes included mode of delivery, endometritis, postpartum hemorrhage requiring transfusion, and maternal deaths. Neonatal outcomes included rates of shoulder dystocia and permanent brachial plexus injury. The willingness-to-pay threshold was set at 100, 000/QALY. Results: In a theoretical cohort of 1.4 million women, waiting four hours instead of two hours led to 322, 253 fewer cesarean deliveries, 6 fewer maternal deaths, 123 fewer postpartum hemorrhages requiring transfusions, and 28, 615 fewer episodes of endometritis. There were 418 more instances of neonatal shoulder dystocia and 14 more cases of permanent brachial plexus injuries with a four-hour threshold. A four-hour threshold leads to 56% more women having a vaginal delivery in our theoretical cohort. Results from our model show that waiting four hours versus two hours to diagnose active phase labor arrest led to increased total QALYs with increased costs, with an incremental cost effectiveness ratio (ICER) below our willingness-to-pay threshold of 100, 000 per QALY. Thus, it was cost effective to wait for at least four hours in the diagnosis of active phase arrest. Multivariable sensitivity analysis demonstrated the model was robust over a wide range of assumptions. Conclusions: Increasing the time threshold from two to four hours for diagnosing active phase labor arrest beyond four centimeters is a cost-effective strategy, resulting in fewer primary cesarean deliveries and improved maternal outcomes, despite a small increase in adverse neonatal outcomes.